Association of Serum Calprotectin (S100A8/A9) Level With Disease Relapse in Proteinase 3–Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 1 (January 2017) - Pepper, Ruth J.; Draibe, Juliana B.; Caplin, Ben; Fervenza, Fernando C.; Hoffman, Gary S.; Kallenberg, Cees G. M.; Langford, Carol A.; Monach, Paul A.; Seo, Philip; Spiera, Robert; William St.Clair, E.; Tchao, Nadia K.; et al.
Abstract : Objective: S100A8/A9 (calprotectin) has shown promise as a biomarker for predicting relapse in antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV). This study was undertaken to investigate serum S100A8/A9 level as a biomarker for predicting future relapse in a large cohort of patients with severe AAV. Methods: Serum levels of S100A8/A9 were measured at baseline and months 1, 2, and 6 following treatment initiation in 144 patients in the Rituximab in ANCA‐Associated Vasculitis trial (cyclophosphamide/azathioprine versus rituximab [RTX] for induction of remission) in whom complete remission was attained. Results: Patients were divided into 4 groups: proteinase 3 (PR3)–ANCA with relapse (n = 37), PR3‐ANCA without relapse (n = 56), myeloperoxidase (MPO)–ANCA with relapse (n = 6), and MPO‐ANCA without relapse (n = 45). Serum S100A8/A9 level decreased in all groups during the first 6 months of treatment. The percentage reduction from baseline to month 2 was significantly different between patients who experienced a relapse and those who did not in the PR3‐ANCA group ( P = 0.046). A significantly higher risk of relapse was associated with an increase in S100A8/A9 level between baseline and month 2 ( P = 0.0043) and baseline and month 6 ( P = 0.0029). Subgroup analysis demonstrated that patients treated with RTX who had increased levels of S100A8/A9 were at greatest risk of future relapse ( P = 0.028). Conclusion: An increase in serum S100A8/A9 level by month 2 or 6 compared to baseline identifies a subgroup of PR3‐ANCA patients treated with RTX who are at higher risk of relapse by 18 months. Since RTX is increasingly used for remission induction in PR3‐ANCA–positive patients experiencing a relapse, S100A8/A9 level may assist in identifying those patients requiring more intensive or prolonged treatment.